Seismic Assessment of RC Arch Bridge: A Case of 2015 Gorkha Earthquake - Gaire, Prakash; Hongwang, Ma (Journal of the Institute of Engineering, 2019)
Nepal Himalayas is one of the most seismic vulnerable zones. The active tectonic action impels the assessment of structures in possible seismic hazards including the bridge structures. This paper presents the impact of the 2015 Gorkha earthquake on the existing reinforced concrete arch bridge at Chobhar, Nepal. A three-dimensional model of the bridge is constructed using Open Sees platform. Nonlinear pushover analysis was performed to find the displacement capacity of the bridge. Ground motion from the main shock of the 2015 Gorkha earthquake is used in this study. Nonlinear time history analysis is performed with three orthogonal ground motions applied in the transverse, longitudinal and vertical direction of the bridge. The study investigates the safety of the bridge scaling up the ground motion to potential PGA in Nepal Himalayas; the result demonstrated the necessity of retrofit to ensure the safety level. Moreover, the horizontal seismic force obtained from the time history analysis is compared with the force obtained from the design code of the bridge. Also, the design force as per the present code (revised code) is presented.